Al-Qur'an Teachers’ Professionalism and Its Contribution to TPACK Development at Madrasah Tsanawiyah - Adlina Avita Martias; Fajar Syarif (Journal of Islamic Education Students (JIES), 2025)
This study aims to explore the professionalism of Al-Qur’an teachers in improving Technological Pedagogical and Content Knowledge (TPACK) at the Madrasah Tsanawiyah level. A descriptive qualitative approach was employed to examine teachers’ understanding of TPACK, professional practices, and challenges in integrating technology into Al-Qur’an instruction. Data were collected through non-participant classroom observations, semi-structured interviews with the principal, Al-Qur’an teachers, educational staff, and students, as well as an analysis of instructional documents. The findings indicate that teacher professionalism is reflected not only in pedagogical and technological competencies but also in spiritual, ethical, and emotional dimensions of teacher–student relationships. Although formal understanding of TPACK varies among teachers, they are able to integrate technology contextually through the use of digital media and tahfīẓ applications while maintaining Qur’anic values. The integration of professionalism and TPACK positively influences students’ learning experiences, particularly in enhancing motivation, engagement, and understanding. However, limitations in technological competence, instructional time, and infrastructure remain significant challenges.